Study of Structural and Compression Properties of Soft Soils in Kunming at Different Moisture Contents - Guo, Wei; Xu, Shiguang; Hong, Tuo; Hao, Shaolei; Chen, Gang (Shock and Vibration, 2023)
The structure of soil refers to the properties and arrangement of soil particles and pores, as well as their interactions, which have a significant impact on the mechanical behavior of soil. Clarifying the strengths and weaknesses of soil structure can effectively ensure engineering safety during designing. In this study, the structural soft soil in the Wujiaba area of Kunming City was studied. A comprehensive structural parameter γ was proposed by analyzing one-dimensional consolidation test data, which consider both the moisture content and yield stress. Due to its high moisture content and lacustrine features, the soft soil in Kunming possessed obvious structural characteristics. As the moisture content increased, the structural characteristics of the soft soil gradually weakened, making it more prone to compression failure. Moreover, the initial consolidation pressure decreased with the increase in moisture content. And the soft soil was more susceptible to deformation failure with higher moisture content. The conclusions drawn from this study have important implications for predicting the settlement of layered soft soil foundations.